(untitled) (مجلة البحوث الأكاديمية, 2026)
Background: Congenital esophageal stenosis (CES) is a rare developmental anomaly with an estimated incidence of 1 in 25,000–50,000 live births [1, 2]. It is often misdiagnosed as acquired strictures or tracheoesophageal anomalies due to overlapping clinical features. Congenital esophageal stenosis (CES) is a rare developmental anomaly presenting with feeding difficulties and esophageal obstruction symptoms in neonates and infants. Case Presentation: We report a 3-day-old full-term female neonate who presented with persistent respiratory distress, choking, and feeding intolerance since birth. Initial radiography revealed nasogastric tube coiling in the upper thoracic esophagus. Contrast-enhanced computed tomography (CT) suggested distal esophageal narrowing with possible bronchoesophageal fistula. Surgical exploration via right thoracotomy revealed a 2 cm fibromuscular stenotic segment without fistulous communication. The segment was resected with primary end-to-end anastomosis. The infant recovered uneventfully and demonstrated normal feeding and growth at 5-month follow-up Conclusion: CES should be considered in neonates with unexplained feeding difficulties and respiratory distress. Early imaging and timely surgical intervention can lead to excellent outcomes.